MENGATASI KESENJANGAN TEORI DAN PRAKTIK DALAM MANAJEMEN PENDIDIKAN: STUDI KOMPARATIF INDONESIA-MALAYSIA - Jumatul Hidayah; Revi Adekamisti; Lukman Asha; Jumira Warlizasusi; Irwan Fathurrochman (Program Studi Manajemen Pendidikan Islam, 2025)
This study explores the integration of educational and management theories to develop adaptive, effective, and sustainable educational governance. The main focus is addressing the gap between theory and practice in educational management within Indonesia and Malaysia, as well as evaluating the application of classical and contemporary management theories in an educational context. Classical management, emphasizing efficiency and hierarchical structure, is considered insufficiently flexible for modern educational needs, necessitating supplementation with human relations theory and transformational leadership that encourage innovation and well-being. This research aims to develop a new conceptual model that merges educational and management theories and provides practical recommendations for educational management in Indonesia. Employing a normative approach through literature review and comparative analysis of educational management policies and practices in Indonesia and Malaysia, findings indicate Malaysia's greater success in outcome-based management through community engagement, while Indonesia faces challenges in consistent policy implementation across regions. The study emphasizes the importance of adaptive managerial strategies based on local social and cultural contexts. It contributes theoretically by offering a new model for educational management and provides practical recommendations, including adaptive strategies and enhanced cross-sectoral and regional collaboration in ASEAN to strengthen education quality and sustainability